2022
DOI: 10.1002/jgm.3292
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Bladder cancer‐associated transcript 2 contributes to nephroblastoma progression

Abstract: Background Nephroblastoma is a common pediatric kidney tumor. Existing evidence has indicated that long non‐coding RNAs (lncRNAs) may be associated with tumorigenesis such as nephroblastoma. However, the contribution of lncRNA bladder cancer‐associated transcript 2 (BLACAT2) to tumorigenesis and the postoperative nephroblastoma prognosis remains unknown. Methods In total, 50 pairs of patient nephroblastoma and corresponding adjacent non‐tumorous tissues were analyzed for BLACAT2 expression. The underlying role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Furthermore, LINC00667 can competitively bind with miR-200b/c/429 to regulate the expression of IKK-β, and subsequently activate the NF-κB pathway in WT, thereby promoting the malignant progression of WT ( 99 ). Zhu et al revealed that the novel BLACAT2/miR-504-3p/Wnt11 axis is related to the occurrence and progression of WT, among which BLACAT2 can absorb miR-504-3p and downregulate Wnt11 ( 101 ). The authors also found that the elevated XIST levels in blood and tissue samples of WT patients are significantly related to TNM staging and a shorter survival time.…”
Section: Biologic Function Of Lncrnasin Wtmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, LINC00667 can competitively bind with miR-200b/c/429 to regulate the expression of IKK-β, and subsequently activate the NF-κB pathway in WT, thereby promoting the malignant progression of WT ( 99 ). Zhu et al revealed that the novel BLACAT2/miR-504-3p/Wnt11 axis is related to the occurrence and progression of WT, among which BLACAT2 can absorb miR-504-3p and downregulate Wnt11 ( 101 ). The authors also found that the elevated XIST levels in blood and tissue samples of WT patients are significantly related to TNM staging and a shorter survival time.…”
Section: Biologic Function Of Lncrnasin Wtmentioning
confidence: 99%
“…Yao et al analyzed the interaction of XIST expression with WT patients’ age, pathological stage, morbidity, and other indicators, and results showed that the high expression of XIST was positively correlated with the incidence of distant metastasis in WT patients, and was also associated with poor WT prognosis ( 100 ). Zhu and colleagues evaluated the potential correlation between the BLACAT2 expression levels and the clinicopathological characteristics of WT patients, and found that there is a strong correlation between high BLACAT2 levels and advanced TNM staging and depth of invasion ( 101 ). In addition, high expression of MYLK-AS1 and XIST are both related to the OS rate of WT patients, and high expression of MYLK-AS1 and XIST predicts a poor patient prognosis ( 102 , 103 ).…”
Section: Biologic Function Of Lncrnasin Wtmentioning
confidence: 99%
“…Bladder cancer-associated transcript 2 (BLACAT2) was first identified to be an oncogene in bladder cancer, which increases tumor lymphangiogenesis and lymphatic metastasis (9,10). It has been previously reported that the expression of BLACAT2 is upregulated in several malignancies, including hepatocellular carcinoma, cervical cancer, and nasopharyngeal carcinoma (11)(12)(13)(14)(15)(16)(17)(18)(19), which suggests that BLACAT2 is closely associated with cancer progression. In fact, BLACAT2 has been demonstrated to aggravate hepatocellular carcinoma via sponging miR-3619-5p, and plays a functional role in modulating radiotherapy resistance in cervical cancer (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The above article, 1 published online on 3 November 2020 in Wiley Online Library (wileyonlinelibrary.com), has been retracted by agreement between the journal's Editor‐in‐Chief, Professor Gening Jiang, and John Wiley and Sons Ltd. The retraction has been agreed owing to the authors’ use of an incorrect cancer cell line during their experiments.…”
mentioning
confidence: 99%